2009
DOI: 10.1007/s00198-009-0991-1
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates and osteoporotic fractures: a cross-design synthesis of results among compliant/persistent postmenopausal women in clinical practice versus randomized controlled trials

Abstract: Compliant/persistent patients in the "real-world" setting benefit from bisphosphonate treatment to a similar extent as patients in randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 46 publications
(46 reference statements)
2
23
0
1
Order By: Relevance
“…Some authors have suggested that a persistent osteoporotic T-score indicates patients at higher fracture risk, who might not be candidates for drug holidays [23]. Similarly some authors have proposed considering a BMD target (such as achieving a non-osteoporotic T-score) as a hypothetical goal of treatment [9], based on the finding that persistent BMD Tscores less than -2.5 after treatment with alendronate indicated a higher risk of subsequent fracture in the FLEX trial [14]. The occurrence of any fracture is still a risk factor for future fractures in both untreated patients [12], and in bisphosphonate treated subjects [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that a persistent osteoporotic T-score indicates patients at higher fracture risk, who might not be candidates for drug holidays [23]. Similarly some authors have proposed considering a BMD target (such as achieving a non-osteoporotic T-score) as a hypothetical goal of treatment [9], based on the finding that persistent BMD Tscores less than -2.5 after treatment with alendronate indicated a higher risk of subsequent fracture in the FLEX trial [14]. The occurrence of any fracture is still a risk factor for future fractures in both untreated patients [12], and in bisphosphonate treated subjects [13].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, osteoporosis agents decrease hip fractures by up to 50%, vertebral fractures by 30-70% (depending on whether detected based on clinical symptoms or morphometry), and nonvertebral fractures by up to 30% [7,8]. When patients are adherent and persistent in their treatments, the reduction in fracture rates has been reported to be similar between clinical trials and observational cohorts [9]. However, no osteoporosis treatment eliminates fractures and some patients that are adherent and persistent in their osteoporosis treatments may remain at elevated risk for future fractures.…”
Section: Introductionmentioning
confidence: 96%
“…В реальной клинической практике, по данным ряда наблюдательных исследований, снижение риска пере-ломов у женщин в постменопаузе с высокой приверженно-стью лечению сопоставимо с данными, полученными в крупных рандомизированных клинических исследованиях [15]. Наоборот, недостаточная приверженность лечению нивелирует доказанную эффективность терапии, проявля-ется значительно более высокой частотой переломов, сни-жением качества жизни, увеличением риска госпитализа-ций, связанных с развитием не только остеопоротических переломов, но и их осложнений (нозокомиальные инфек-ции и тромбоэмболия легочной артерии) [16].…”
Section: показанияunclassified
“…Unfortunately, poor medication compliance is associated with a reduced clinical benefit and increase in hip fracture risk [10][11][12][13][14]. Previous studies have identified that high compliance with osteoporosis medications within the first year of initiation is associated with a significant reduction in fracture rates, [11] with up to a 60% reduction in hip fracture rates [14,15]. However, while there is consistent evidence that better medication compliance reduces fracture risk; the effect estimates reported are inconsistent.…”
Section: Introductionmentioning
confidence: 99%